Strategi Dinas Lingkungan Hidup Dalam Pengelolaan Sampah Di Kabupaten Jombang - Dinda Amalia Arrahma; Rachmawati Novaria; Adi Soesiantoro (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2024)
Waste management in Jombang Regency, East Java, is a strategic issue that requires comprehensive and sustainable handling. This research aims to analyze the strategy of the Jombang Regency Environmental Agency (DLH) in waste management, focusing on the strengths, weaknesses, opportunities, and threats faced. The research method used is qualitative with SWOT analysis techniques, involving interviews, observation, and documentation. The results of the analysis show that waste management in Jombang, strengths, namely, local government support, the achievement of the Banjardowo landfill, 14 Adipura awards, cross-sector collaboration, the Waste Bank program, and the Jogoroto TPS 3R strategy reflect the success of waste management in Jombang Regency. Weaknesses, namely, low waste management services, increasing volume, lack of participation, depending on APBN/APBD, not optimal sorting, limited human resources, lack of socialization, uneven TPS. Opportunities, namely, Potential to increase public participation through education, collaboration with the private sector for innovation, development of Waste Bank and digitalization, stronger regulations for TPS construction, and application of new technology for efficiency and sustainability. Threats, namely, The increase in waste volume can cause landfills to be exceeded, dependence on unstable APBN/APBD funding, changes in government policies, inconsistent community responses, and cross-sector coordination challenges.